Supply Chain Collaboration, Last Mile Delivery Performance and Customer Experience: An Analysis of the Boundary Condition of Supply Chain Integrity - Makafui, Rosemary Agboyi (International Journal of Supply Chain and Logistics, 2025)
Purpose: The primary objective of this study is to comprehensively examine the relationship between supply chain collaboration and customer experience in the Ghanaian delivery services market. Methodology: The research employs a survey, quantitative, descriptive, and positivist approach as a research strategy. Convenience and purposive sampling techniques were used to obtain a sample size of 400. The study employed primary data gathered with questionnaires as the data collection tool. A total of 450 questionnaires were sent to senior managers in the manufacturing and service industries in Ghana. Out of these, 400 questionnaires were returned, with 280 from manufacturing businesses and 120 from service organizations. Findings: The results support a positive relationship between supply chain collaboration and customer experience. There is strong support for the positive impact of supply chain collaboration on last-mile delivery performance. The study finds that last-mile delivery has a significant positive effect on customer experience. The results support the mediating role of last-mile delivery in the relationship between supply chain collaboration and customer experience. Interestingly, the moderating effect of supply chain integrity on the relationship between supply chain collaboration and customer experience was not supported. Investment in collaborative technologies is essential for modern companies aiming to enhance supply chain efficiency. Unique Contribution to Theory, Policy and Practice: The study recommends that companies must prioritize the development and strengthening of collaborative relationships across their supply chains, establishing collaborative performance metrics and incentive systems can align goals across the supply chain, invest in technologies that optimize last-mile delivery efficiency, such as route optimization software and real-time tracking systems and consider partnerships with specialized last-mile delivery providers and explore innovative delivery models such as crowdsourced delivery or autonomous vehicles.